Particle tracking simulation of marine debris using Lagrangian discrete and mesh spatial discretization in Banda Aceh waters - Koko Ondara; Guntur Adhi Rahmawan; Syahrul Purnawan (Depik, 2021)
Ocean dynamics has a direct impact on the distribution of objects or dissolved particles such as marine debris. Hydrodynamic studies are currently an important tool to identify the potential pollution in the region. Data were collected from March to September 2019 in the northern waters of Banda Aceh. Wind data were obtained using AWS and bathymetry data were collected using the single beam echosounder. The results showed that the wind direction on the coast of Banda Aceh City was dominant towards the Northwest and Northeast with a maximum speed of 9 m/s. Wind direction will highly influence the sea surface currents dynamics that lead to longshore currents and radiation currents occur in coastal areas.Keywords:Marine debrisWasteFishery